Extrashift of a Resident of Psychiatry in COVID-19 Respiratory Emergency - Kashefinejad, Shayan (Journal of Pediatric Nephrology, 2020)
Hard days have come for medical staff. Before the storm, we took some of our dearest colleagues, as well as some of our compatriots, with us and made us sad, but there is no mourning. We have to work even harder than before and fight. Keywords: Medical Resident; COVID-19; Emergency Room.